Surgical strategy for locally advanced gastric cancer - Binay, Thakur; Mukti, Devkota; Sapkota, Bishal (Nepalese Journal of Cancer, 2018)
Gastric cancer is endemic in China, Japan, Korea, Brazil and Former Soviet Union. Patients are diagnosed usually in locally advanced stage. Endoscopy, PET-CT, Endoscopic ultrasound and staging laparoscopy are the tools for proper evaluation of such patients. Locally advanced gastric cancer (T2-4N0 or T any N+) requires multimodality treatment including surgery. Surgical strategy requires gastrectomy with D2 nodal dissection.